Agrarian Law Reform Based on Good Land Governance in Indonesia: A Normative Legal Analysis - Suyanto, Suyanto (Institute for Law and Economics Studies, 2026)
Agrarian law reform in Indonesia is an urgent necessity amid increasing land ownership inequality, weak legal certainty, and widespread agrarian conflicts. The Constitutional Court's Decision Number 185/PUU-XXII/2024 regarding the term of Building Use Rights (HGB) and Business Use Rights (HGU) in the Capital City of Nusantara (IKN) reinforces the urgency of national agrarian law reform. This article aims to examine the direction of agrarian law reform based on Good Land Governance (GLG). Through an analysis of positive legal norms, doctrines, and good governance principles, this study emphasizes that agrarian law reform must integrate the principles of transparency, accountability, participation, justice, and sustainability. These findings reinforce the idea that Indonesian agrarian law must transform from a paradigm of control to a paradigm of equitable management